2020
DOI: 10.3390/ma13163496
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Hybridization Process on the Mechanical and Thermal Properties of Polyoxymethylene (POM) Composites with the Use of a Novel Sustainable Reinforcing System Based on Biocarbon and Basalt Fiber (BC/BF)

Abstract: The presented work focuses on the assessment of the material performance of polyoxymethylene (POM)-based composites reinforced with the use of a biocarbon/basalt fiber system (BC/BF). The use of BC particles was aimed at eliminating mineral fillers (chalk, talc) by using fully biobased material, while basalt fibers can be considered an alternative to glass fibers (GF). All materials were prepared with the same 20% filler content, the differences concerned the (BC/BF) % ratio. Hybrid samples with (25/75), (50/5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 75 publications
5
8
0
Order By: Relevance
“…The highest melting temperature ()Tm is observed in POM/3 wt% polymer composite. A similar trend was observed by Andrzejewski et al 32 on bio carbon and basalt fiber reinforced POM. It is observed that the crystalline structure increased in composite results in increasing melting point.…”
Section: Resultssupporting
confidence: 89%
“…The highest melting temperature ()Tm is observed in POM/3 wt% polymer composite. A similar trend was observed by Andrzejewski et al 32 on bio carbon and basalt fiber reinforced POM. It is observed that the crystalline structure increased in composite results in increasing melting point.…”
Section: Resultssupporting
confidence: 89%
“…The combination of two kinds of fillers in a single matrix can show advantages of both fillers. The following different combinations of fillers can be used to produce hybrid composites: banana/glass [ 12 ], kenaf/glass [ 13 ], wood/glass [ 14 ], palm/kenaf [ 15 ], and biocarbon/basalt [ 16 ]. Hybridization can help to change the properties of different composite applications.…”
Section: Introductionmentioning
confidence: 99%
“…The necessity for Synthetic Fibers (SFs) is advancing globally, as it is a highly significant form of material for fiber-reinforced composite structures. The growing demand for lightweight and unique composite materials increases the need for SFs due to their excellent characteristics [ 1 , 2 , 3 ]. There is strong competition between Synthetic Fibers and Natural Fibers (NFs) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%